One touch of scandal [large type] - Carlyle, Liz (Thorndike Press large print core, 2011)
When she is accused of murdering her employer, governess Grace Gauthier begs the mysterious--and possibly dangerous--Lord Ruthveyn to help her unmask the real killer and clear her name.